An Overview of Hypertension Incidence Among: A Retrospective study - Agus Salim; Wiwiek Hidayati Jaya; Ernawati Ernawati (An Idea Health Journal, 2025)
Hypertension remains a public health issue that significantly contributes to increased rates of morbidity, disability, and mortality. This condition is often referred to as a “silent killer” because many patients are unaware of their condition until complications arise. This study aims to determine the general profile of hypertension prevalence among outpatients at Syekh Yusuf Gowa Regional General Hospital in 2025. The study employed a descriptive quantitative design with a retrospective approach through the analysis of medical records. The study population consisted of all outpatients diagnosed with hypertension during the period of January–December 2025. A total sampling technique was used, yielding a sample of 54 respondents. Data were analyzed univariately and presented in the form of frequency distributions and percentages. The results of the study showed that the largest age group was 46–55 years old, comprising 18 respondents (33.3%); the majority were female, comprising 31 respondents (57.4%); the most common educational level was high school, comprising 19 respondents (35.2%); and the most common occupation was homemaker, comprising 17 respondents (31.5%). Based on blood pressure classification, stage 1 hypertension was found in 28 respondents (51.9%), stage 2 hypertension in 19 respondents (35.2%), and hypertensive crisis in 7 respondents (12.9%). The most common comorbid condition was diabetes mellitus, affecting 14 respondents (25.9%). The conclusions of this study indicate that the prevalence of hypertension among outpatients at Syekh Yusuf Gowa Regional General Hospital is dominated by the pre-elderly age group, women, and stage 1 hypertension. Enhanced education, routine screening, and risk factor management are needed to prevent further complications.